PENGARUH MERK DAN KUALITAS PRODUK CCTV TERHADAP KEPUTUSAN PEMBELIAN PELANGGAN DI PT FOCUS CENTRAL SECURINDO - zhong, ericsen; Heryenzus, Heryenzus (SCIENTIA JOURNAL, 2021)
PT Focus Central Securindo is one of the companies engaged in the electronics distributor located at Ruko Palam Spring where PT Focus Central Securindo was established in 2016. The technique used in this study is saturated sampling used is the distribution of questionnaires. The method for analytical in this study is multiple regresion which includes: validity test, reliability test, normality test, multicholine meaning test, heteroscedastic test, determination test and partial test. And we have the results showed that the brand partically affected 3.405 > 1.983 of the t table, so that 0.00 < 0.05 alpha. While the partical effect of product quality is 8.368 > 1.983 from t table. And with the purchase decision we have a signifcant influence of 106,188 > 3,080 from F table, then 0.00 < 0.05. And the signifcance value of the simultaneous test. And the study results on consumer satisfaction showed that the R2 effect of 81.9%. that means the brand and product quality had a significant effect.